COMMON THEMES BETWEEN THE WORKS OF JOHN DONNE AND JOHN MILTON - Zahro Qodirova Zafarovna; Maftuna Qodirova Davronovna (Western European Studies, 2024)
This article considers the work of Enlightenment poets who depicted the real life of people in seventeenth century England in their works. The author of the article presented about the creative heritage of the poets and their literary directions. Several poems of poets were also analyzed.
Keywords: Metaphysical; elegy; conceits